(3GdQSGdI GdfGaYI HGdCOdI GdhGbYIs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMeO EdgGekG CeG HYO , aEfg HdZfG fRGY LQi Hjf GdCUMGH , dGjMSf eKdg ef Chdi GdCdHGH s
(3BNQgG (B:s
(3dfchf ai CeQfG Ydi HUjQI , hfSjQ ai WdH gOGjJfG CMSf SjQI , hGdUdGI Ydi eMeO QShd Gddg Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG TQhM PGJ bjeIs
(3ai JHjjf GdRjOjI hePGgHge s
(3hPcQ aVGFd CejQ GdeDefjf hJHjf ef NQL ef GdTjYI GdeMbjf ef GdEeGejI hGdHGWfjI hGdeWQaI s
(3cJHJ HYV GdYfGhjjf HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds